Resection of the carina and oesophagus for malignant tumours of the oesophagus or tracheobronchial tree. - Ikeda, T (1984)
Resection of the oesophagus together with the bifurcation of the trachea has been performed in three patients with oesophageal carcinoma or mucoepidermoid carcinoma of bronchial origin. Two patients had an uneventful recovery and survived five and 10 months but one patient died in the immediate postoperative period from aspiration pneumonia and respiratory failure. There has been no report of combined resection of the oesophagus and carina since Thompson's paper in 1973, but it appears to be indicated occasionally in patients with tracheobronchial or oesophageal malignancy, particularly when it is associated with an oesophagobronchial fistula.